Collision Tumor of the Thyroid Gland: Primary Squamous Cell and Papillary Thyroid Carcinoma - Warman, Meir (International Scholarly Research Network, 2011)
Introduction. Collision tumor of the thyroid gland is defined when independent and histologically distinct tumors coexist within the gland. The presence of both papillary and squamous cell carcinoma in the thyroid gland is unusual. Suggested etiologies include embryonic remanents of squamous epithelium, chronic inflammation, or thyroid malignancies promoting squamous metaplasia. Case Presentation. An elderly patient presented with a rapid enlargement of a long-standing right thyroid nodule. The tumor was locally invasive and unresectable. Pathology revealed the diagnosis of papillary and squamous cell carcinoma of the thyroid gland. Possible primary sites for squamous cell carcinoma in upper aerodigestive tract were excluded. The patient outcome was fatal although palliative chemoradiotherapy. Discussion. Collision tumor of papillary and squamous cell carcinoma of the thyroid gland is a rare entity that may imply bad prognosis, as to the presence of the squamous portion. The best treatment includes resection of the tumor; unfortunately it is not possible in most cases.